Synthesis and Biodegradation Studies of Low‐Dispersity Poly(acrylic acid). Issue 13 (17th March 2022) - Barbon, Stephanie M.; Carter, Matthew C. D.; Yin, Ligeng; Whaley, C. Matthew; Albright, Vurtice C.; Tecklenburg, Ron E.
Abstract: Poly(acrylic acid) (PAA) is produced on an industrial scale and widely‐used in applications such as personal care products and cleaning formulations that end up "down‐the‐drain." Relatively high molecular weight PAA is considered poorly biodegradable, but little is known about the biodegradability of low molecular weight PAA at the wastewater treatment plant according to current regulatory and industrial Organization for Economic Co‐operation and Development (OECD) standards. The synthesis, separation, and characterization of a series of ultralow dispersity PAA oligomers (i.e., Đ < 1.10) in the molecular weight range M n ≈ 350–1200 Da and the results of biodegradability testing are reported. Miniaturized, high‐throughput screening studies in a parallel respirometer reveals a strong trend toward lower biodegradation at higher molecular weight; these results are confirmed and expanded using standardized method OECD 301F. Biodegradability reaches ≈40% at M n = 380 Da, ≈26% at M n = 770 Da, and ≈17% at M n = 1190 Da for discrete polyacid oligomers. These data not only shed light on potential biodegradation mechanisms for linear PAA, but also may inspire the future design of biodegradable PAA‐containing macromolecules. Abstract : New insights into the fate of widely‐used polymers will accelerate the design of environmentally‐friendly materials. Here, a modern synthesis approach provides precise control over poly(acrylic acid) molecular weights with near‐perfect dispersities. Comprehensive characterization of polymer microstructure and biodegradation testing by both high‐throughput and industrially‐relevant methods yield an improved understanding of the biodegradation/molecular weight relationship.